Історичний аспект формування колекції дендрарію Ботанічного саду НЛТУ України - Kendzora, N. Z.; Ivchenko, A. I.; Khomiak, T. V.; Bliusiuk, N. L.; Koliada, L. B. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
The beginning of forestry science in the west of Ukraine, important figures of the Regional School of Forestry, the history of the creation of the arboretum of the Botanical Garden of the Ukrainian Forestry National University, the formation of a dendrological collection, unique centuries-old trees are mentioned. The main stages of development of the dendroflora collection, its dynamics and current state are also shown. The main directions of research on the basis of the arboretum are outlined